2022
DOI: 10.1093/jmicro/dfac049
|View full text |Cite
|
Sign up to set email alerts
|

Filovirus helical nucleocapsid structures

Abstract: Filoviruses are filamentous enveloped viruses belonging to the family Filoviridae, in the order Mononegavirales. Some filovirus members, such as Ebola virus (EBOV) and Marburg virus (MARV), cause severe hemorrhagic fever in humans and non-human primates. The filovirus ribonucleoprotein complex, called the nucleocapsid, forms a double-layered helical structure in which a non-segmented, single-stranded negative-sense RNA genome is encapsidated by nucleoprotein (NP), viral protein 35 (VP35), VP24, VP30, and RNA-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…Additional reviews with more specific information related to the nucleocapsid and RNP structure of viruses within this family can be found in [ 23 , 24 ].…”
Section: Structure Of the Nucleocapsid Of -Ssrnavmentioning
confidence: 99%
“…Additional reviews with more specific information related to the nucleocapsid and RNP structure of viruses within this family can be found in [ 23 , 24 ].…”
Section: Structure Of the Nucleocapsid Of -Ssrnavmentioning
confidence: 99%
“…LLOV possesses a nonsegmented, single-stranded, negative-sense RNA genome. Its viral genomic RNA (vRNA) encodes at least seven proteins: a nucleoprotein (NP), a polymerase cofactor (viral protein 35 [VP35]), a matrix protein (VP40), a glycoprotein (GP), a transcriptional activator (VP30), a nucleocapsid associated protein (VP24), and an RNA-dependent RNA polymerase (L) ( 1 , 5 , 6 ). A morphological analysis of the virus-like particles (VLPs) of the LLOV showed that the virus has a characteristic filamentous structure, like other filoviruses ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…A morphological analysis of the virus-like particles (VLPs) of the LLOV showed that the virus has a characteristic filamentous structure, like other filoviruses ( 7 ). The nucleocapsid, which is located at the center of the filamentous particles, comprises a helical structure of the NP–vRNA complex associated with VP35, VP30, VP24, and L and is responsible for transcribing and replicating the vRNA ( 6 , 8–10 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations